Bioerosion in the Late Eocene Discocyclina discus sowerbyi (Nuttall, 1926) in Bayat Area, Indonesia: Implications for Paleoecology - Rahmawati, Diana; Surjono, Sugeng Sapto; Barianto, Didit Hadi; Rahardjo, Wartono (Universitas Gadjah Mada, 2024)
This paper discusses about the bioerosion discovered in carbonate tests of Discocyclina discus sowerbyi (Nuttall, 1926), a large benthic foraminifera from the Priabonian (Late Eocene). The study material was sampled from the Gamping beds in the Wungkal-Gamping Formation in Bayat, Indonesia. We discovered four bioerosional trace fossils from three different ichnogenera demonstrate bioerosion from the surface test analysis. Oichnus simplex and Oichnus paraboloides are ichnogenus Oichnus diagnostic drilling holes that are often found on the surface. Caulostrepsis isp. exhibits the presence of uncomplicated U-shaped borings. The observed formation of drill holes can be mostly linked to the predatory behaviour of gastropods, while other trace fossils are predominantly associated with the burrowing activities of worms. The occurrence of well-preserved individual tests exhibiting no signs of bioerosion is infrequently observed in D. discus sowerbyi. In addition, bioerosion occurs more frequently in the microspheric generation than in the megalospheric generation. This research also demonstrates for the first time in Indonesia that parrotfish bite marks have developed on individual tests of the microspheric generation of D. discus sowerbyi. The taphonomic characteristics exhibited by the bioeroded and encrusted D. discus sowerbyi specimens can serve as reliable paleoecological indicators for sediment deposition occurring at an intermediate to high sedimentation regime. The occurrence of larger foraminifera with some bioerosional trace fossil highly proficient at documenting shallow marine sclerobionts.